Karakterisasi Kadar Air Dan Penyerapan Iodin Karbon Dari Tempurung Buah Nipah Sebagai Adsorben Gas H2S - Meta Aprilia Saputri; Dhau Aprilia Hakim (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2021)
Air pollution requires proper handling so that the impact can be reduced. Nipah fruit shell contains high cellulose and lignin so that carbon from nipah fruit shell needs to be implemented as an adsorbent to reduce the concentration of Hydrogen sulfide (H2S) gas produced from fish waste. The purpose of this study was to determine the characterization of carbon from nipah fruit shells as H2S gas absorbers with the effect of time variations of 10 minutes, 15 minutes and 20 minutes. The method of absorption of H2S absorption using iodine absorption with iodometric titration. The sampling process went through several stages, such as the carbonization process, carbon characterization process, and H2S gas adsorption using carbon that had been characterized by water content and iodine absorption. This research resulted in the production of carbon from nipa palm shell as an H2S gas absorber which has a water content characterization of 1.0651% and an iodine absorption capacity of 615.6105 mg/g so that it can adsorb H2S gas with an initial concentration of 64 ppm until it reaches the lowest concentration of 5.538 ppm.